Health journalism: a bibliometric analysis of research themes and future directions - Feng, Shi (Frontiers in Communication, 2024)
The body of health journalism research literature remains scattered across various disciplines and requires comprehensive understanding. This study aims to enhance researchers’ comprehension of the field, by presenting a systematic review of SSCI-indexed articles. Findings reveal two peaks in health journalism research from 1994 to 2023: during the 2009 H1N1 influenza and the COVID-19 outbreak. Using bibliographic coupling analysis, it was possible to define 10 major research themes from the review. They were: How health stories are framed in the news; How audiences engage with health information online; How constructive journalism can improve the news reporting of public health crisis; How fact-checking can improve the news reporting of public health crisis; How health stories are framed from science journalism perspective; Why citizen journalism is significant in health news reporting; How health journalists perceive their journalistic role; Who serves as the news source for health news reporting; How health professionals impact health news reporting; and How peace journalism can be used for health news reporting on vulnerable populations. This research provides insights into the current state of health journalism research and outlines potential areas for further exploration in health journalism, spanning topics such as women and other marginalized communities in health reporting.